Association of depression and anxiety with clinical, sociodemographic, lifestyle and environmental factors in South Asian and white European individuals at high risk of diabetes. Issue 9 (30th June 2019) - Razieh, C.; Khunti, K.; Davies, M. J.; Edwardson, C. L.; Henson, J.; Darko, N.; Comber, A.; Jones, A.; Yates, T.
Abstract: Aim: To investigate the prevalence and correlates of depressive and anxiety symptoms within South Asian and white European populations at high risk of developing Type 2 diabetes. Methods: Data were collected at baseline, and at 12, 24 and 36 months from 1429 white European individuals (age 64±7 years, 35.8% women) and 160 South Asian individuals (age 59±9 years, 30.6% women) who were at high risk of Type 2 diabetes and who took part in two Type 2 diabetes prevention trials in Leicestershire, UK. The Hospital Anxiety and Depression Scale was administered during each study visit. Clinical, sociodemographic, lifestyle and environmental data were collected. Results: At baseline, the burden of depressive symptoms varied by ethnic group and gender, with 9.9% of white European men, 14.9% of white European women, 23.6% of South Asian men and 29.2% of South Asian women exceeding the cut‐off score for mild‐to‐severe depression. During the course of the study and after adjustment for clinical, sociodemographic, lifestyle and environmental factors, depressive symptoms remained higher in the South Asian compared to the white European participants [score higher by 1.5, 95% CI 0.9–2.1]. Levels of anxiety were also higher in the South Asian participants, although associations were attenuated after adjustment. Social deprivation, BMI, proximity to fast‐food outlets and physical activity were correlates for depression in both the South Asian and white European participants. Conclusions: A higher burden of depressive symptoms was consistently evident among the South Asian individuals, even after adjustment for multiple covariates. It is important to understand both the reasons why these differences are present, to help reduce health inequalities, and whether higher levels of depressive symptoms affect the uptake of and retention rates in diabetes prevention programmes in South Asian communities. What's new?: Depression is associated with Type 2 diabetes with a direction of causation that has been suggested to be bidirectional in nature. South Asian individuals at high risk of Type 2 diabetes reported higher depressive symptoms compared to white Europeans. This was irrespective of a number of clinical, sociodemographic, lifestyle or environmental factors. The development and evaluation of culturally appropriate methods for treating depression need to be integrated into diabetes prevention services in the future. Integrating depression screening and treatment into these services, with particular focus on minority populations, may improve engagement and retention.